Art and Politics : Between Purity and Propaganda - Segal, Joes (Book collections on Project MUSE., 2016)
This book explores the place of art and artists under a number of different political regimes of the twentieth and twenty-first centuries, traveling around the world to consider how art and politics have interacted and influenced each other in different conditions.